Impacto do projeto re-ciclo na coleta seletiva do município de Fortaleza - Osorio, Pedro Pinheiro (2024)
This work addresses the waste management system of the Municipality of Fortaleza, focusing on the door-to-door selective collection of recyclable materials project, Re-ciclo. Through a case study, the impact caused during the first year of operation of the new phase of the project will be presented, where waste management equipment, Ecopoints, and three Associations of Recyclable Material Collectors were incorporated into the Re- cycle. The National Solid Waste Policy, Law No. 12,305/2010, prioritizes recycling as one of the final destinations for urban solid waste, making it therefore important to develop projects and public policies aimed at this activity and ensuring a more sustainable urban space. The results of this work are an analysis of interviews and questionnaires applied to participants in the execution of the project, Fortaleza City Hall, startup Solos and Collectors Associations, and the amount of recyclable waste collected in establishments and residences registered in Re-ciclo, thus allowing, understand the impact on the selective collection scenario in the city of Fortaleza. Keywords: Solid waste, Selective collection, Recycling.